Verification and analysis of meteorological early warning of geological hazards during precipitation of Typhoon "MEGI" - Yin YANG; Hongjun BAO; Tao PENG (暴雨灾害, 2019)
"MEGI", the No.17 typhoon in 2016, generated many geological hazards (geo-hazards) in Fujian and Zhejiang Provinces and caused many death and property loss on 28th September. Based on hazard data from hazard management system of China Meteorological Administration and China Institute of Geo-Environmental Monitoring, and combined the precipitation observation, precipitation forecast from many sources, hazard-affected body fragility and exposure degree, this study made analysis to the geo-hazards generation factor, verified in quantitative to the warning effect of Geo-hazards model of National Meteorological Centre (NMC), and summarized the experience of gridded quantitative precipitation forecast using. Result shows that, Precipitation was the main cause of geo-hazards. national meteorological early warning of geological Hazards' hit and miss rate were 67.8% and 11.1%, which were better than model. The hit rate of second generation model better than the first might because of using geological information in high resolution, the first and second generation model had the problem of false alarm, the first generation of geo-hazards model of NMC had the problem of forecasting highest level risk at places with high risk of geological Hazard in condition of had or will have extraordinary rainstorm. Gridded quantitative precipitation forecast had the advantage of higher resolution and could make quantitative precipitation forecasting in given place than rank precipitation forecast made by forecaster, which were more suitable for meteorological early warning of geo-hazards, but attentions should be paid to the defect of forecasting ability in places such as terrain complex area. Conclusions were based on typhoon "MEGI", more analysis and verification are needed to testify whether the result was regularity in future.